Análisis de Factores Determinantes en la Producción de Queso: Caso de Estudio en Huaytará-Huancavelica - Huaman Jurado, Rodrigo (2024)
This study aims to analyze the determinants of cheese production, focusing on Huaytará, Huancavelica. The research, carried out with 31 milk producers during rainy and dry seasons, revealed that 80.6% of the producers are married, suggesting the influence of family stability. In addition, 67.7% are women, indicating their significant participation in the cheese activity. With 41.9% having secondary education, the need to improve technical capacity is highlighted. Although the majority own their own home (96.8%), the low minimum income (S/. 950) raises economic concerns. The average age of 46.42 years indicates considerable experience in the industry. Milk production focuses on cows and goats (45.2%), but only 12.9% are engaged in cheese production. Pasture-based feeding affects milk composition, and 61.3% of producers milk fewer than 10 cows, reflecting low productivity. Cheese production is mostly low quantity (64.5% produce less than 10 kg/day), with local distribution (61.3%). The average monthly income is S/. 1,729.35, but the minimum income is low. Despite challenges in productivity and education, the province shows potential for socioeconomic improvements. In conclusion, Huaytará faces challenges in productivity and education, but stands out for its family stability and the participation of women in the cheese industry, suggesting opportunities for socioeconomic improvement.